Studying the online comprehension of written sarcasm: an eye-tracking investigation - Turcan, Alexandra (2016)
Theories of sarcasm comprehension make different predictions regarding how various linguistic and contextual factors might affect the processing of written sarcasm. Modular theories predict a processing difficulty associated with sarcastic remarks (the standard pragmatic model), especially unfamiliar ones (the graded salience hypothesis) as compared to literal language, irrespective of contextual factors. Interactive theories however, predict that contextual factors can facilitate sarcasm processing, for example echoing an antecedent (the echoic mention theory), making the speaker’s expectation explicit (the implicit display theory), or a variety of other factors (the constraint satisfaction model). The present research systematically manipulated utterance literality (Experiments 1-7), utterance familiarity (Experiments 2 and 6), echo (Experiments 1 and 2), speaker’s expectation (Experiments 4 and 6), and speaker’s communicative style (Experiment 7), and used eye-tracking while reading to investigate their effect on sarcasm processing. Results indicated that (1) sarcastic comments were not always more difficult to process than literal ones, (2) utterance familiarity, echoing a contextual antecedent, and knowing the speaker’s communicative style, all aided sarcasm comprehension, while, (3) making the speaker’s expectation explicit did not. Taken together, the present results are better accommodated by interactive theories of language processing, and more specifically by the constraint satisfaction model. However, the constraint satisfaction model is not a testable theory in its current formulation, hence suggestions are made for ways of better specifying it, in order to develop it into a testable and comprehensive theory of sarcasm processing.